THE EFFECTIVENESS OF MIND MAPPING LEARNING METHODS TO IMPROVING STUDENT LEARNING OUTCOMES IN LEARNING AL-QUR'AN HADITH - Majid, Mellania Afnani; Fattah, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The learning method is a technique used by educators to students in carrying out learning in order to achieve learning objectives. Therefore, educators need to choose appropriate learning methods. This study aims: 1) To determine the implementation of the mind mapping method in learning Al-Qur'an Hadith, 2) To determine the effectiveness of the mind mapping method in learning Al-Qur'an Hadith, 3) To determine the supporting and inhibiting factors of the mind mapping method in learning Al-Qur'an Hadith. This research is quantitative research. The data were obtained from the results of observations, documentation and learning outcomes tests. Before testing the hypothesis, the validity and reliability tests were carried out as a prerequisite test. For the normality test, the Kolmogorov Smirnov test was used, and the results were that the data were not normally distributed, therefore, the homogeneity test was not carried out. The data analysis technique for hypothesis testing uses the Wilcoxon Rank Sum Test, all of which are calculated using SPSS version 26.0. The results showed (1) the learning process using the mind mapping method showed a positive response from students, (2) there was a significant difference in student learning outcomes between the experimental class and the control class, it can be seen from the average post-test result of the control class of 58, 2 and the experimental class average is 80, (3) The use of mind mapping learning methods is quite effective in improving student learning outcomes in the Al-Qur'an Hadith subjects which is supported by the results of the Wilcoxon Rank Sum Test significance value of 0.000 which is smaller than 0.05 which means H 0 is rejected.